2006
DOI: 10.1080/13651820600917294
|View full text |Cite
|
Sign up to set email alerts
|

Acute pancreatitis: an under-recognized risk of percutaneous transhepatic distal biliary intervention

Abstract: The risk of acute pancreatitis after distal PTBI is under-recognized and should be considered as a consent issue in patients scheduled for distal PTBI and when post-procedure abdominal pain ensues.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 21 publications
0
19
0
Order By: Relevance
“…Acute Pancreatitis.-Acute pancreatitis that occurs after biliary drainage (Fig 9) has a reported prevalence of 4%-6% (19), and distal biliary manipulation, stent placement across the ampulla of Vater, and placement of internal and/or external biliary drainage catheters involve a greater risk. Therefore, it is essential that interventionalists inform their patients of this risk when informed consent for PTBI is obtained and that they stay alert to the possible development of acute pancreatitis in the event that severe abdominal pain ensues after the intervention.…”
Section: Nonvascular Complicationsmentioning
confidence: 99%
“…Acute Pancreatitis.-Acute pancreatitis that occurs after biliary drainage (Fig 9) has a reported prevalence of 4%-6% (19), and distal biliary manipulation, stent placement across the ampulla of Vater, and placement of internal and/or external biliary drainage catheters involve a greater risk. Therefore, it is essential that interventionalists inform their patients of this risk when informed consent for PTBI is obtained and that they stay alert to the possible development of acute pancreatitis in the event that severe abdominal pain ensues after the intervention.…”
Section: Nonvascular Complicationsmentioning
confidence: 99%
“…5 A review of literature by Al-Bahrani AZ et al found 11 reported cases of pancreatitis as a complication of percutaneous transhepatic interventions (PTBI) and documented five patients with pancreatitis following PTBI in their original research. 6 An interesting observation was a risk of pancreatitis comparable to ERCP. This risk is greater with distal interventions than with proximal procedures.…”
Section: Discussionmentioning
confidence: 99%
“…The application of a negative pressure is a novel approach to severe abdominal sepsis and laparostomy management with a view to preventing compartment syndrome and fatal sepsis, and it can lead to complete abdominal wound closure. patients with a high mortality risk [9]; it complicates 9% of ERCP in OLT patients [4], whereas no specific data are available on PTBD procedures in the OLT population.…”
Section: Discussionmentioning
confidence: 99%
“…Acute pancreatitis after PTBD in untransplanted patients with biliary strictures occurs in about 6.6% of patients with a high mortality risk [9]; it complicates 9% of ERCP in OLT patients [4], whereas no specific data are available on PTBD procedures in the OLT population.…”
Section: Introductionmentioning
confidence: 99%